A label-free aptasensor for turn-on fluorescent detection of ochratoxin a based on SYBR gold and single walled carbon nanohorns. (May 2021) - Guo, Zhijun; Tian, Jing; Cui, Chengbi; Wang, Yan; Yang, Huanhuan; Yuan, Ming; Yu, Hansong
Abstract: Ochratoxin A (OTA), is one of the most commonly found mycotoxins in food. It is primarily produced by Aspergillus ochraceus and Penicillium verrucosum . OTA can causes serious damages to liver and kidney, increases the teratogenicity, and has been considered as a potential carcinogen (group 2 B). In this study, we demonstrated a new detection system for the detection of OTA using fluorescence biosensing according to an anti-OTA aptamer and fluorescence quencher using single-walled carbon nanohorns (SWCNHs). In the presence of OTA, the OTA-specific aptamer underwent the conformation change from a random coil to an antiparallel G-quadruplex. The latter one was resistant to being adsorbed onto SWCNHs, leading to the pertection of the fluorescence of SYBR Gold. As a result, the remained fluorescent intensities correlated with the concentrations of OTA. The detection limit of OTA was 2.3 ng/ml, meanwhile the linear detection range was 5–500 ng/ml, with a satisfactory linear correlation (R 2  = 0.992) of the fluorescence intensity and the logarithm of OTA concentrations. The aptasensor was subjected to quantify the concentration of OTA in red wine samples. As a result, this label-free aptasensor was suitable for the test of OTA in food samples. Highlights: We demonstrated a label-free and "turn-on" fluorescent aptasensor for OTA detection. This method presence advantages including low cost, highly sensitivity and simple performance. This label-free aptasensor was suitable for the test of OTA in food samples. The principle can also be further developed for the detection of other targets.